2021
DOI: 10.1038/s41467-021-25943-3
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule junction spontaneously restored by DNA zipper

Abstract: The electrical properties of DNA have been extensively investigated within the field of molecular electronics. Previous studies on this topic primarily focused on the transport phenomena in the static structure at thermodynamic equilibria. Consequently, the properties of higher-order structures of DNA and their structural changes associated with the design of single-molecule electronic devices have not been fully studied so far. This stems from the limitation that only extremely short DNA is available for elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The studies of individual DNA junctions bonded through hydrogen bond, π‐π stacking interactions have also revealed a wealth of information on electron transport, [24, 60] thermoelectric effects [61] hybridization dynamics [62] et al. Moreover, recent studies have shown that DNA zipper structure not only has excellent electrical conductivity but more importantly exhibits self‐restoring capability, which is valuable for the constriction of feasible and reproducible molecular junctions [44b] …”
Section: Supramolecular Junctions With Non‐covalent Interactionsmentioning
confidence: 99%
“…The studies of individual DNA junctions bonded through hydrogen bond, π‐π stacking interactions have also revealed a wealth of information on electron transport, [24, 60] thermoelectric effects [61] hybridization dynamics [62] et al. Moreover, recent studies have shown that DNA zipper structure not only has excellent electrical conductivity but more importantly exhibits self‐restoring capability, which is valuable for the constriction of feasible and reproducible molecular junctions [44b] …”
Section: Supramolecular Junctions With Non‐covalent Interactionsmentioning
confidence: 99%
“…Schematic illustration of the scanning tunneling microscopy break junction (STM‐BJ) measurements. Reproduced with permission [107] . Copyright 2021, The Author(s).…”
Section: Detection Of Dnamentioning
confidence: 99%
“…Since the inventions of break junction techniques, the electrical properties of oligonucleotides, including DNA [ 89 , 90 ], RNA [ 91 ] and RNA: DNA Hybrids [ 92 ], have been explored in the molecular junctions. It was found that the single-molecule conductance of these oligonucleotides is very sensitive to the molecular length [ 93 ], the helical conformation [ 94 ], the base sequence [ 95 ], and the environmental surroundings [ 96 ]. For instance, a single base pair mismatch in the short double stranded DNA (dsDNA) can cause the single-molecule conductance changing up by one order of magnitude [ 97 ].…”
Section: Genetic Materials Detectionmentioning
confidence: 99%